Reclaiming the Heritage of Saints Serge and Bacchus: Towards a Quixotic Gay-Affirmative, Pro-Animal, Vegetarian Christianity - Long, Ronald (Theology & sexuality, 2011)
An event in the life of Tchaikovsky occasions the possibility of the development of a wisdom prefigured in the story of the martyrdom of Sts Serge and Bacchus—a Christian view of the world which embraces gay legitimacy and commends vegetarianism. This wide-ranging essay seeks first to retrieve from its cultured despisers a vision of sex as flowering in enduring affectionally grounded relationships; and then contextualizes that vision within a theology that celebrates an inclusive creaturely enjoyment of other creatures as the proper end of life, and thinks of God as an implicate of prayerful living in the light of a hope against hope—in full acknowledgment of mortality and vulnerability—for a perfected world, to which gay sexual love, like all love, and vegetarianism are both pointers.